2012
DOI: 10.3390/molecules17055733
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Biopolymers on the Rheological Behavior of Surimi Gel

Abstract: Abstract:The objective of this study was to investigate the effect of selected biopolymers on the rheological properties of surimi. In our paper, we highlight the functional properties and rheological aspects of some starch mixtures used in surimi. However, the influence of some other ingredients, such as cryoprotectants, mannans, and hydroxylpropylmethylcellulose (HPMC), on the rheological properties of surimi is also described. The outcome reveals that storage modulus increased with the addition of higher le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
(85 reference statements)
0
4
1
2
Order By: Relevance
“…This finding shows that cobia mince produces a slightly higher yield of surimi (61.53 %) than silver catfish (60 %) after 4-5wash cycles in the same NaCl concentration. Sarker et al (2012), found yields from minced flesh at 56.16 % for grass carp, 43.00 % for sin croaker, and 45.00 % for mackerel; all of which were lower than the results obtained.…”
Section: Yield Of Surimi Productioncontrasting
confidence: 58%
See 2 more Smart Citations
“…This finding shows that cobia mince produces a slightly higher yield of surimi (61.53 %) than silver catfish (60 %) after 4-5wash cycles in the same NaCl concentration. Sarker et al (2012), found yields from minced flesh at 56.16 % for grass carp, 43.00 % for sin croaker, and 45.00 % for mackerel; all of which were lower than the results obtained.…”
Section: Yield Of Surimi Productioncontrasting
confidence: 58%
“…This is because increasing the amount of water used for washing usually causes greater protein loss and decreased surimi yield. Sarker et al (2012), found a lower surimi yield for tilapia (18.99 %) when the ratio of water to mince was 4:1 with four wash cycles. Thus, a logical approach to achieving optimal wash cycle effects and maximal surimi yield is to lower the water-to-mince ratio while increasing wash duration and the number of cycles.…”
Section: Yield Of Surimi Productionmentioning
confidence: 89%
See 1 more Smart Citation
“…Besarnya kadar air pada surimi berpengaruh terhadap konsentrasi tepung yang ditambahkan. Menurut Sarker et al (2012) untuk surimi yang mempunyai kadar air 86% minimum jumlah tepung yang ditambahkan adalah sebesar 10%, namun semakin banyak tepung yang ditambahkan akan menghasilkan produk yang elastisitasnya berkurang. Kadar abu surimi ikan patin sebesar 0,53±0,03%, masih dalam kisaran persyaratan mutu SNI 01-2694-2006 yaitu maksimum 1%.…”
Section: Hasil Dan Pembahasan Karakteristik Surimi Ikan Patin (Pangasunclassified
“…Penambahan t epung karaginan dan konjak dimaksudkan untuk memperoleh tekstur yang mendekati elastisitas dengan cumi-cumi. Pada dasarnya konjak merupakan hidrokoloid yang tidak dapat membentuk gel tanpa adanya alkali (Sarker et al, 2012). Karaginan dan konjak dapat bekerja secara sinergis sehingga dapat mendorong pembentukan gel dari konjak melalui interaksi segregatif dari kedua polimer tersebut, sehingga dapat membentuk gel dengan tekstur yang lebih kuat dan elastis (Brenner, Tuvikene, Fang & Matsukawa, 2015).…”
Section: Formulasi Cumi-cumi Analogunclassified